Friction and wear properties of a high Nb-containing TiAl alloy against WC-8Co, Si3N4, and GCr15 in an unlubricated contact. (March 2019) - Cheng, Fang; Lin, Junpin; Liang, Yongfeng
Abstract: Friction and wear properties of a high Nb-containing TiAl alloy against WC-8Co, Si3 N4, and GCr15 in an unlubricated contact were investigated under various friction and wear conditions. The counterface material plays a key role in the friction and wear properties of the high Nb-containing TiAl alloy. The Si3 N4 /TiAlNb pair had the highest average friction coefficient caused by the abrasive wear and adhesive wear. The applied temperature had a strong effect on the friction coefficient of the Si3 N4 /TiAlNb and GCr15/TiAlNb pair. The WC-8Co/TiAlNb pair has the stable average friction coefficient under various friction and wear conditions due to the abrasive wear. Highlights: Friction and wear properties of a high Nb-TiAl alloy were studied in an unlubricated contact. The counterface material played a key role in the friction and wear properties of the Nb-TiAl alloy. The Si3 N4 /TiAlNb pair had the highest friction coefficient due to abrasive and adhesive wear. The temperature had a strong effect on the friction coefficient of the alloy against GCr15 and Si3 N4 . The WC-8Co/TiAl pair had a stable friction coefficient under all wear conditions for abrasive wear.